A Studi Literatur: Implementasi Pijar Sekolah sebagai Media Pembelajaran Biologi di Era Digital - maury asyura; Relsas Yogica (LP2M UIN Ambon, 2026)
This study aims to analyze and synthesize the implementation of School Spotlight as a Biology learning medium in the digital age through a literature review. The research method used was a Systematic Literature Review (SLR), which analyzed various relevant scientific articles on Pijar Sekolah, digital learning, Learning Management Systems (LMS), and Biology education. The results of the study indicate that the implementation of Pijar Sekolah offers various benefits in supporting biology learning, such as improving access to learning, supporting self-directed learning, providing diverse digital learning resources, and aiding in the visualization of abstract biological concepts. An analysis based on the End User Computing Satisfaction (EUCS) dimensions shows that aspects such as content, accuracy, format, ease of use, and timeliness play a role in supporting the effectiveness of the platform’s use. Nevertheless, the implementation of Pijar Sekolah still faces several challenges, such as limited internet connectivity, technical system glitches, limited access to technological devices, and low digital literacy among users. These findings indicate that improvements in system quality, services, and technological infrastructure support are necessary to optimize the use of Pijar Sekolah in Biology education in the digital age.